SAHRUR DAN POLIGAMI (Kritik Epistemologi) - Mohammad Fateh (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2009)
The discussion of polygamy is always interesting to peel. Both groups pro or reject polygamy “as if ” race to show the public the reasons and rationale for them. Not infrequently “war” clause (more precisely) the interpretation of polygamy verses (Surah An-Nisa ‘: 3) coloring the debate discourse above. Sahrur is regarded as one of the leaders who is in passing considered the anti-polygamy and doing a lot of criticism of the dirty practices of polygamy among Moslems. However, if further research is inconsistency in the logic of his interpretations. On the one hand, Sahrur is against polygamy, even if it is only allowed for those who can penetrate the boundaries and strict rules of polygamy. However, on the other hand the logic of interpretation, identify the opposite direction. In addition, it seems that in the interpretation of paragraph polygamy (Surah An-Nisa ‘: 3) Sahrur exclude asbabun Nuzul or revelation causes, so it is impressed it is pulled out from the roots of the verse contextuality